Five additions to the genus Acourtia (Asteraceae: Mutisieae) - Cabrera R., Leticia (Instituto de Ecología, A.C., 1992)
Revisionary studies of Acourtia have resulted in the discovery of five new species, A. oaxacana, A. mexiae, A. pulchella, A. gentry and A. gracilis. All the new taxa are endemic to Mexico. The new species are described and their morphological affinities to other species of the genus discussed.